Educational aspects in Malik Bin Nabi's thought: An analytical study - Mudawi, Muslim AbdulQadir (Journal of Educational and Psychological Sciences, 2023)
The research aims to identify some of the educational, social, and economic aspects of the Algerian, Malik bin Nabi used the two methods: historical to identify the factors that formed his thought in general and the educational aspects of his life in general and descriptive analysis of the contents of some of his statements in books and articles Lectures and working papers from educational aspects, and the research reached several results, the most important of which are: Malik bin Nabi's possession of a well- defined educational thought that can be applied in Islamic societies in the social, and economic aspects, as well as the strong link between the Religion and society, to consider that religion is the main motivation for educational thought, and to submit it to a specific educational work program according to proposals that can be applied.
Keywords: educational aspects; thought; Malik Bin Nabi; Algeria